AL-ḤAWĀLAH DALAM KAJIAN TAFSIR DAN HADIS - Achmad Baiquni (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2018)
This paper discusses about al-Ḥawālah, namely the transfer of debt. This study has a very important purpose for the continuation of human interaction in daily life, it is very important for academics to learn about al-Ḥawālah studies in the Qur’an and Hadith, so that it can be used as a source of legal assistance for Muslims. The author can consider al-Ḥawālah, namely the transfer of debt from the debtor (al-mudīn) to others who are burdened with others with a kafālah that can only collect dependents in the hands of the guarantor (kāfil) without being moved, while the debt is still in the responsibility of al-mudīn.